Analysis of infilled steel frames subjected to lateral loading. (2023) - Pradeep, A.R.; Rangaraj, C.; Jayaramappa, N.
Abstract: In Recent days Earthquake resistant design of structure has earned a lot of scope as Earthquake has become more common. Lateral loading behaviour and energy absorption capacity of monolithic Steel framed structures is significantly affected by Presence of infill which adds to the bracing of the structure, Researchers developed new methods of seismic analysis to analyse the behaviour of structure during occurrence of an Earthquake. Performance based seismic design gives methodology for accessing the performance of structure occupancy, life safety or Collapse prevention level. A non-linear static pushover analysis can be used to analyse the inelastic response of structure to lateral load or displacement. In the present research a 3D model of G + 8 story steel framed building is considered for seismic design and performance evaluation. The model was analysed using ETABS software by response spectrum method for zone V according to IS 1893–2016. The performance is accessed by Capacity Spectrum Method using non-linear pushover analysis. The result of all models are analysed and compared in terms of base shear, story displacement, pushover curve, spectrum curve, performance point of the structure. Overall performance of the structure is found in safer limits.